Comparative analysis between bloom’s and Malik Badri’s taxonomies of thinking process - Abdullah, Norillah; Syed Hassan, Sharifah Sariah (2011)
In common practice of education, we create learning objectives and assessment questions based on Bloom taxonomy of behavioral objectives. Bloom taxonomy has assisted teachers in transforming learning from low to high order thinking. Unfortunately, Bloom taxonomy has encountered a shortcoming of the assumption of men as merely the body and mind without addressing the spiritual entity. For Muslims to adapt Bloom taxonomy in planning and learning process reflects the ignorance of the fitrah or primordial of men which is the most crucial aspect in Islam. Therefore this taxonomy has to be revisited from the perspective of Muslim model of thinking. Further educational objectives in cognitive domain should be explored. This research aims at highlighting the assumption of metaphysical foundation of Bloom Taxonomy which is contradicting with the Islamic metaphysic. It also attempts to discover the differences between Bloom and Malik Badri taxonomy of thinking process which resulted from different metaphysical foundations and it’s implication to the Muslim educational setting. This research aims to develop Muslim model of thinking for educational objectives in cognitive domain. The methodology of this research is based on the philosophical analysis and historical development of Bloom taxonomy and Malik Badri in order to identify the main differences between their taxonomies of the thinking process.